If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(X + 5m + 4) = 0 Reorder the terms: 6(4 + X + 5m) = 0 (4 * 6 + X * 6 + 5m * 6) = 0 (24 + 6X + 30m) = 0 Solving 24 + 6X + 30m = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + 6X + -24 + 30m = 0 + -24 Reorder the terms: 24 + -24 + 6X + 30m = 0 + -24 Combine like terms: 24 + -24 = 0 0 + 6X + 30m = 0 + -24 6X + 30m = 0 + -24 Combine like terms: 0 + -24 = -24 6X + 30m = -24 Add '-30m' to each side of the equation. 6X + 30m + -30m = -24 + -30m Combine like terms: 30m + -30m = 0 6X + 0 = -24 + -30m 6X = -24 + -30m Divide each side by '6'. X = -4 + -5m Simplifying X = -4 + -5m
| 9=5+2t | | 2[2y+5]=26 | | c=cx+n | | X^9/x^2 | | 2xy+6a=8x | | v^2+6-7=0 | | 19n=190 | | 3=2w-1 | | 7=v-8 | | -4k+2(5k-6)=-3k-38 | | 1/2(2)-3=y | | 2/3×9/20 | | -7v=140 | | D+30=9 | | C+24=-10 | | (8y-5w)= | | A-8=-14 | | 3q+1=7 | | (X^2+15-8x)=0 | | 5/11b=15 | | 8(x+1)=2(3x+5) | | H/5-19=2 | | 11(b-875)=517 | | x^3+3x^2=13x+9 | | 6log(x-3)=11 | | x+(x+1)-(x+2)+(x+3)= | | 0=v^2-10v+24 | | 6(x-4)=-3(x-4) | | A/9=123 | | f=-2+4x-1+-1x | | 6z^2=-19z-10 | | H--184/22=30 |